Implementation of the iterative refinement method for computing the approximate greatest common divisor of univariate polynomials [electronic resource] - Aimi Salwana Ab Rahman, 1985-; Nor'Aini Aris (2014)
Thesis (Sarjana Sains (Matematik)) - Universiti Teknologi Malaysia, 2014